Design assessment of a horizontal shell and tube latent heat storage system: Alternative to fin designs. (1st December 2021) - Sodhi, Gurpreet Singh; Kumar, Vishnu; Muthukumar, P.
Highlights: Developed design alternatives to conventional finned and non-finned LHS systems. Effective PCM and heat transfer surface area distribution along the system length. Cylindrical/converging conical/diverging conical shells and HTF tubes analysed. Charging/discharging time reduction by 37%/47.3% than cylindrical shell and tube. Converging conical shell and converging HTF tube proposed as the best alternative. Abstract: In the present study, the charging and discharging performances of a horizontal shell and tube latent heat storage (LHS) system are analysed. The effective heat capacity approach is adopted to develop a numerical model using sodium nitrate as the phase change material (PCM) and air as the heat transfer fluid (HTF). The study proposes design alternatives to conventional shell and tube LHS systems by varying the PCM volume distribution and the surface area of heat transfer along the length. A novel design methodology is proposed, wherein, the outer shell of the LHS system is optimized into a cone and the cross-section of the HTF tube is varied. Based on the optimal shell dimensions, seven different designs having cylindrical/converging conical/diverging conical shells and cylindrical/converging/diverging cross-sections of the inner HTF tube are developed for a fixed PCM volume and heat transfer surface area. The LHS system with converging shell and converging cross-section HTF tube is found to have optimal performance with 37% and 47.3% reduction in charging and discharging times over the conventional cylindrical shell and tube system. The system is also compared with a fin and non-finned cylindrical shell and tube system at different inlet charging and discharging temperatures. The melting and solidification contours and melt fraction plots show a more uniform rate of natural convection and conduction heat transfer along the length of the proposed optimal design which is projected as an alternative to longitudinal fin design due to similar charging/discharging performances. Graphical abstract: Image, graphical abstract